Electrochemical property studies of carbon nanotube films fabricated by CVD method as anode materials for lithium-ion battery applications. (February 2015) - Gao, Hongxu; Hou, Feng; Zheng, Xuerong; Liu, Jiachen; Guo, Anran; Yang, Deming; Gong, Yuxuan
Abstract: Carbon nanotube films (CNT-1 and CNT-2) were fabricated in a vertical CVD gas flow reactor with water sealing. CNT-1 films consist of ordered crystalline carbon nanotubes, while CNT-2 are defective carbon nanotube films. The films are flexible and transferrable and can be used as binder-free anodes for lithium-ion batteries (LIB). Electrochemical measurements show that CNT-2 possess a reversible capacity of 452 mA h g −1 under a current density of 30 mA g −1, which is higher than that of CNT-1 (375 mA h g −1 ) under the same current density. In addition, the CNT-2 shows a reversible capacity of 107.9 mA h g −1 after 500 cycles at a current density of 3000 mA g −1, while 82.1 mA h g −1 for CNT-1 under the same condition. Good correlations between morphological factors, defective structure and electrochemical performance are observed. Highlights: As-synthesized carbon nanotube films are continuous and free-standing. The films can be used as flexible, binder-free electrode for lithium-ion battery. Defective carbon nanotube is favorable to enhance reversible capacity of CNT film.